What Is Karyotype Coding and Why Is Genomic Topology Important for Cancer and Evolution? - Ye, Christine J.; Stilgenbauer, Lukas; Moy, Amanda; Liu, Guo; Heng, Henry H. (Frontiers in Genetics, 2019)
While the importance of chromosomal/nuclear variations vs gene mutations in diseases is becoming more appreciated, less is known about its genomic basis. Traditionally, chromosomes are considered the carriers of genes, and genes define bio-inheritance. In recent years, the gene-centric concept has been challenged by the surprising data of various sequencing projects. The genome system theory has been introduced to offer an alternative framework. One of the key concepts of the genome system theory is karyotype chromosomal coding: chromosome sets function as gene organizers and the genomic topologies provide a context for regulating gene expression and function. In other words, the interaction of individual genes, defined by genomic topology, is part of the full informational system. The genes define the “Parts Inheritance,” while the karyotype and genomic topology (the physical relationship of genes within a three-dimensional nucleus) plus the gene content defines “System Inheritance.” In this mini-review, the concept of chromosomal coding will be briefly discussed, including: 1) the rationale for searching for new genomic inheritance, 2) chromosomal or karyotype coding (hypothesis, model, and its predictions), and 3) the significance and evidence of chromosomal coding (maintaining and changing the system inheritance-defined bio-systems). This mini-review aims to provide a new conceptual framework for appreciating the genome organization-based information package and its ultimate importance for future genomic and evolutionary studies.